Model EOQ Perishable Item dengan Penurunan Minat Pembeli Menggunakan Kedatangan Uniform - Ginola, Andes; Angel Olivia Benedikta; Edwin Sutiana (Journal of Research in Industrial Engineering and Management, 2025)
Inventory is a company asset in the form of idle resources or unused resources that needs to be minimized. One type of inventory is perishable items. Perishable items are products with a limited life cycle. This limited life cycle affects consumer interest in purchasing the product, leading to a decrease in consumer interest as the item approaches its expiration date. This results in a reduction in inventory value as purchases and product expiration occur. This study changes the arrival speed of goods from simultaneous to uniform, introducing a constant arrival speed (R) in the model formulation. The development of this model focuses on inventory systems for perishable items with a decline in buyer interest as the product life cycle decreases and products arrive uniformly. It is found that uniform arrival reduces the total cost compared to simultaneous arrival.